QMDE: A quarterly empirical model for the Danish economy. A stock-flow consistent approach - Mikael Randrup Byrialsen; Hamid Raza; Sebastian Valdecantos (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
In this paper, we present a quarterly model for the Danish economy while focusing on the main assumptions behind the model and the construction of the databank behind the model. The purpose of the model is to build a platform for analysing the interdependencies between the real and financial sides of the economy, which is an important feature of the stock-flow consistent approach. The model parameters are estimated using quarterly Danish data over the period 2005-2020. We validate the model from both an empirical and theoretical perspective. From an empirical point of view, we numerically solve the model and compare the model results with the original data to ensure that the model is able to capture the dynamics of the economy. From a theoretical point of view, we introduce a standard shock to public spending and explore whether the response of the economy is in line with what is predicted by the theory. In both cases, we find that the model fulfils the intended objective.
Keywords: E17; E12; F41; 330; Empirical Stock-Flow Consistent Models; Denmark; Open Economy